2016
DOI: 10.1021/acs.jafc.6b01272
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Xylanase and Debranching Enzymes Specific to Wheat Arabinoxylan Improve the Growth Performance and Gut Health of Broilers

Abstract: Arabinoxylan (AX) is the major antinutritional factor of wheat. This study evaluated the synergistic effects of xylanase and debranching enzymes (arabinofuranosidase [ABF] and feruloyl esterase [FAE]) on AX. During in vitro tests, the addition of ABF or FAE accelerated the hydrolysis of water-soluble AX (WE-AX) and water-insoluble AX (WU-AX) and produced more xylan oligosaccharides (XOS) than xylanase alone. XOS obtained from WE-AX stimulated greater proliferation of Lactobacillus brevis and Bacillus subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…The inclusion of AXOS encourages beneficial bacteria and protects against pathogenic bacteria [34,35], which consequently enhances gut health. Lei et al documented that dietary Xyl, Abf, and feruloyl esterase improved gut health [36]. Pettey et al also indicated that adding 0.05% β-mannanase and arabinoxylooligosaccharides led to an improved blood IGF-I concentration in growing and finishing pigs [37].…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of AXOS encourages beneficial bacteria and protects against pathogenic bacteria [34,35], which consequently enhances gut health. Lei et al documented that dietary Xyl, Abf, and feruloyl esterase improved gut health [36]. Pettey et al also indicated that adding 0.05% β-mannanase and arabinoxylooligosaccharides led to an improved blood IGF-I concentration in growing and finishing pigs [37].…”
Section: Resultsmentioning
confidence: 99%
“…comprising 15–35% of each plant’s dry weight 1 . Xylan is a heterogeneous polysaccharide consisting of a backbone of β-1,4-xylose units that are attached by side chains such as arabinose, methyl glucuronic acid, and acetate groups 2 . A series of enzymes is essential when xylan is completely degraded to monosaccharide, mainly including endo-β-xylanases (EC 3.2.1.8) and β-D-xylosidases (EC 3.2.1.37).…”
Section: Introductionmentioning
confidence: 99%
“…This xylanase has potential utility in animal feed to improve nutrient digestibility and growth performance for animals, especially broiler chickens and hens [53]. …”
Section: Discussionmentioning
confidence: 99%